Reported Consumption of Low-Calorie Sweetener in Foods, Beverages, and Food and Beverage Additions by US Adults: NHANES 2007–2012. Issue 9 (28th June 2018) - Malek, Angela M; Hunt, Kelly J; DellaValle, Diane M; Greenberg, Danielle; St. Peter, John V; Marriott, Bernadette P
Abstract: Background: Low-calorie sweeteners (LCSs), artificial sweeteners, or high-intensity sweeteners are incorporated into foods, beverages, and food and beverage additions (FBAs). Many prior studies have focused on LCS beverage consumption, but not included LCS consumption from foods or FBAs. Objectives: We aimed to describe the prevalence of LCS consumption by US adults, and to examine the relation between intake of products containing LCSs and macronutrients. Methods: Two nonconsecutive 24-h dietary recalls from NHANES 2007–2012 and the National Cancer Institute usual intake method were used to estimate prevalence of LCS intake from foods, beverages, and FBAs, and macronutrients among US adults aged ≥19 y ( n  = 14, 098, weighted n  = 218, 391, 752) in a cross-sectional study. The prevalence of LCS consumption from reported foods, beverages, and FBAs among US adults was examined by sociodemographic characteristics and body mass index (BMI). Logistic regression estimated ORs and 95% CIs for associations between sociodemographic characteristics and LCS use (overall and in foods, beverages, and FBAs). Results: Among adults, 47.8% reported intake of ≥1 food, beverage, or FBA containing LCSs over 2 d. Intake was higher among: women non-Hispanic whites, college graduates or higher, and those with higher income and obese BMIs ( P  < 0.001). Intake of beverages containing LCSs was higher for ages 51–70 y than 19–30 y and those with overweight and obese BMIs ( P  < 0.001) than for normal-weight individuals. Calories, carbohydrate, and sugar intake were lower and fiber was higher in LCS-consumers than in nonconsumers. Specifically, calories from beverages were lower in those who reported LCS intake. Conclusions: Individuals reporting LCS consumption demonstrated lower total energy intake than did individuals without LCS intake. Although the main source of LCSs in the US adult diet was beverages (31.9%), we found that FBAs also present a significant contribution (25.2%), surpassing food (9.3%). This enables targeted understanding of national consumption of these products as well as dietary education and intervention opportunities.